True umbilical cord knot, an emergency during labor - Begoña Díaz de la Noval; Iris Porcel Llaneza; Manuel Rueda Sepúlveda; Francisco Javier Ferrer Barriendos; Carmen Fernández Blanco (Clinical Case Reports, 2019)
Abstract An umbilical cord knot is an unexpected event that should not change obstetric approach for delivery.